Quartz glass crucible and its manufacturing method

A three-layered quartz glass crucible with controlled bubble sizes and densities addresses deformation and contamination issues in CZ method silicon single crystal production, ensuring stable and high-quality crystal pulling.

JP7621116B2Active Publication Date: 2025-01-24MOMENTIVE TECH YAMAGATA CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2020218491
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-28
Publication Date
2025-01-24
Estimated Expiration
2040-12-28

AI Technical Summary

Technical Problem

Existing quartz glass crucibles used in the CZ method for silicon single crystal production face issues with deformation and contamination due to bubble size variations and centrifugal forces during high-temperature operations, leading to decreased yield and quality instability.

Method used

A three-layered quartz glass crucible structure is introduced, comprising an outer opaque layer with smaller bubbles and higher density, a middle opaque layer with larger bubbles and lower density, and a transparent inner layer with minimal impurities, along with a manufacturing process that controls bubble size and density through staged pressure adjustments during melting.

Benefits of technology

The crucible structure stabilizes the crucible's shape and prevents deformation during high-temperature operations, maintaining consistent quality and preventing inward or outward collapse, thereby enhancing the yield and reliability of silicon single crystal production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007621116000003
    Figure 0007621116000003
  • Figure 0007621116000004
    Figure 0007621116000004
  • Figure 0007621116000005
    Figure 0007621116000005
Patent Text Reader

Abstract

To provide a quartz glass crucible that can prevent deformation of collapsing inside or sinking outside of a quartz glass crucible when the crucible is heated with high temperature and has stable quality on a size of bubble existing in an outer layer, and to provide a method for manufacturing the same.SOLUTION: A quartz glass crucible includes: a transparent inner layer 4; and an outer layer 2 disposed on an outer side relative to the transparent inner layer and formed opaque by including bubbles. The outer layer includes: a first outer layer 2A; and a second outer layer 2B disposed on an inner side relative to the first outer layer. The bubbles existing in the first outer layer have an average diameter that is smaller than a diameter of bubbles existing in the second outer layer. The first outer layer has a bulk density that is larger than the bulk density of the second outer layer.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a quartz glass crucible for pulling silicon single crystals by the Czochralski method (hereinafter referred to as the "CZ method"). [Background technology]

[0002] The CZ method is widely used to grow silicon single crystals. In this method, a seed crystal is brought into contact with the surface of molten silicon contained in a quartz glass crucible, and the crucible is rotated while the seed crystal is pulled upward while rotating in the opposite direction, thereby forming a single crystal at the bottom end of the seed crystal.

[0003] Meanwhile, in order to produce high-quality silicon single crystals for semiconductor devices at low cost, it is necessary to increase the single crystal yield in a single pulling process, and to do so, a crucible with a stable shape that will not deform during long-term operation is required.

[0004] In the deformation of the crucible, the so-called inward collapse, in which the straight body part of the crucible collapses toward the silicon melt, is particularly problematic. A heat shield plate, known as a hot zone, is provided around the ingot near the surface of the silicon melt, and if the straight body part of the crucible collapses inward, this inward collapsed part may come into contact with the heat shield plate. Since the crucible rotates during pulling of the single crystal, the straight body part of the crucible comes into contact with the heat shield plate while rotating, which causes defects such as further deformation of the crucible, damage to the heat shield plate, and a decrease in production yield due to crucible fragments being mixed into the silicon melt.

[0005] In order to prevent deformation of the crucible at high temperatures, Patent Document 1 discloses a quartz glass crucible which comprises an opaque layer containing air bubbles provided on the outer surface side of the crucible, and a transparent layer from which the air bubbles have been removed provided on the inner surface side of the crucible, and the opaque layer at least in the straight body portion has a bubble distribution in which the average diameter of the bubbles gradually decreases from the outer surface to the inner surface.

[0006] According to the quartz glass crucible disclosed in Patent Document 1, the size of the bubbles in the opaque layer gradually decreases from the outside to the inside, improving toughness and suppressing deformation such as inward collapse at high temperatures. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2015-127287 A Summary of the Invention [Problem to be solved by the invention]

[0008] The method for manufacturing a quartz glass crucible disclosed in Patent Document 1 includes a step of depositing a first natural quartz powder (average particle size of 200 to 400 μm) having a first average particle size on the surface of a mold, a step of depositing a second natural quartz powder (average particle size of 100 to 200 μm) having an average particle size smaller than the first average particle size, and a step of depositing a third natural quartz powder (average particle size of 50 to 150 μm) having a third average particle size smaller than the second average particle size.

[0009] However, when melting the quartz powder accumulated in the mold, the mold is rotated at high speed, and the small quartz powder accumulated inside the crucible moves outward due to centrifugal force, making it difficult to create an ideal change in bubble size. In addition, because the size of the bubbles is controlled by the particle size of the quartz powder, the size of the bubbles is affected by particle variations, and there was an issue that the same quality could not be maintained depending on the crucible.

[0010] The present invention has been made under the above circumstances, and aims to provide a quartz glass crucible and a manufacturing method thereof that can prevent the quartz glass crucible from collapsing inward and sinking outward when heated to high temperatures, and that has stable quality in terms of the size of bubbles present in the outer layer. [Means for solving the problem]

[0011] The quartz glass crucible of the present invention, made to solve the above-mentioned problems, is a quartz glass crucible for pulling a single crystal by the Czochralski method, and comprises a transparent inner layer and an outer layer arranged outside the transparent inner layer and formed to be opaque by containing gas bubbles, the outer layer having a first outer layer and a second outer layer arranged inside the first outer layer, the average diameter of the gas bubbles present in the first outer layer is smaller than the diameter of the gas bubbles present in the second outer layer, and the bulk density of the first outer layer is greater than the bulk density of the second outer layer. In addition, in the outer layers, it is preferable that the thickness of the second outer layer is the same as or greater than the thickness of the first outer layer. In addition, in the outer layers, it is desirable that the average diameter of the bubbles present in the first outer layer is 16 to 56 μm, and the average diameter of the bubbles present in the second outer layer is 21 to 100 μm. In addition, in the outer layer, the bulk density of the first outer layer is 1.96 g / cm 3 More than 2.08g / cm 3 and the bulk density of the second outer layer is 1.74 g / cm 3 More than 1.88g / cm 3 It is desirable that the following:

[0012] According to this configuration, in the second outer layer, the wall thickness expansion rate increases due to bubble expansion at high temperatures, improving adhesion to the carbon susceptor, making it difficult for the crucible to tip over. Also, in the first outer layer, the viscosity increases at high temperatures, so that outward sinking deformation can be prevented even if the second outer layer expands.

[0013] Furthermore, the method for manufacturing a quartz glass crucible according to the present invention, which has been made to solve the above-mentioned problems, comprises the steps of rotating an inner member of a crucible forming mold around an axis and supplying a glass raw material powder to the inside of the inner member to form an outer layer, supplying a glass raw material powder to the inside of the outer layer to form an inner layer to form a crucible forming body, and heating and melting the crucible forming body from the inside to form a quartz glass crucible, characterized in that, during the heating and melting of the outer layer, the pressure within the inner member is changed in two stages to form a first outer layer and a second outer layer having different average diameters of bubbles contained therein.

[0014] According to this method, in forming the outer layer, a molded body is formed using quartz powder of the same particle size, and the pressure inside the mold when melting the molded body is changed to form a first outer layer and a second outer layer having different bubble diameters. Therefore, the bubble diameter can be easily controlled, and the problem that the same quality cannot be maintained depending on the crucible can be solved. Effect of the Invention

[0015] According to the present invention, it is possible to provide a quartz glass crucible and a manufacturing method thereof that can prevent the crucible from collapsing inward and sinking outward when heated to high temperatures, and that has stable quality in terms of the size of bubbles contained in the outer layer. [Brief description of the drawings]

[0016] [Figure 1] FIG. 1 is a cross-sectional view of a quartz glass crucible according to the present invention. [Diagram 2] FIG. 2 is an enlarged cross-sectional view of a portion of the quartz glass crucible of FIG. [Diagram 3] FIG. 3 is a schematic diagram of an apparatus for manufacturing the quartz glass crucible of FIG. [Figure 4] FIG. 4 shows a flow for manufacturing the quartz glass crucible of FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS Hereinafter, an embodiment of a quartz glass crucible for pulling silicon single crystals according to the present invention will be described with reference to the drawings. Fig. 1 is a cross-sectional view of a silica glass crucible 1 according to the present invention. Fig. 2 is an enlarged cross-sectional view of a part of the silica glass crucible of Fig. 1. This quartz glass crucible 1 is used, for example, in a single crystal pulling apparatus (not shown), and is used in the apparatus while being held by a carbon susceptor (not shown). That is, in the single crystal pulling apparatus, raw silicon is melted in a quartz glass crucible 1, and a silicon single crystal is pulled up from the molten liquid.

[0018] The quartz glass crucible 1 is formed, for example, with a diameter (caliber) of 810 mm and has a crucible bottom 9 having a predetermined curvature (first curvature), a bottom corner 8 formed around the crucible bottom 9 and having a predetermined curvature (second curvature), and a straight body portion 7 extending upward from the bottom corner 8. As shown in Fig. 1, an outer layer 2 is formed on the outside of a crucible 1, and an inner layer 4 is formed on the inside. The outer layer 2 is an opaque layer (a layer that becomes opaque due to the inclusion of air bubbles) made of natural raw material quartz glass, and the outer layer 2 is further composed of a first outer layer 2A formed on the outside and a second outer layer 2B formed on the inside of the first outer layer 2A. Also, on the inside of the second outer layer 2B, a transparent inner layer 4 is formed, made of high-purity synthetic raw material quartz glass (or natural raw material quartz glass) that comes into contact with molten silicon when pulling up a silicon single crystal.

[0019] Here, opaque means that a large number of bubbles (pores) are present in the quartz glass, making it appear cloudy. The natural quartz layer means a silica glass layer manufactured by melting natural raw materials such as quartz, and the synthetic quartz layer means a silica glass layer manufactured by melting synthetic raw materials synthesized, for example, by hydrolysis of silicon alkoxide.

[0020] In the outer layer 2, the second outer layer 2B is formed to have a thickness equal to or greater than the thickness of the first outer layer 2A. Preferably, the ratio of the thickness of the first outer layer to the second outer layer is 5:5 or more and 4:6 or less. The first outer layer 2A and the second outer layer 2B have different diameters of bubbles present in each layer. Specifically, the average bubble diameter of the first outer layer 2A is in the range of 16 to 56 μm, and the bulk density of the first outer layer 2A is, for example, 2.03 g / cm. 3 On the other hand, the average bubble diameter of the second outer layer 2B is in the range of 21 to 100 μm, and therefore the bulk density of the second outer layer 2B is, for example, 1.81 g / cm 3 is formed.

[0021] That is, the first outer layer 2A, which is the outermost layer in the outer layer 2, has a smaller bubble diameter, and the second outer layer 2B, which is the innermost layer, has a larger bubble diameter. The first outer layer 2A is also formed to have a smaller bulk density than the second outer layer 2B. As a result, in the second outer layer 2B, the wall thickness expansion rate increases due to bubble expansion at high temperatures, improving adhesion to the carbon susceptor, making it difficult for the crucible 1 to collapse inward. Also, in the first outer layer 2A, the viscosity increases at high temperatures, so that outward sinking deformation can be prevented even if the second outer layer 2B expands in the thickness direction.

[0022] 2, the outer layer 2 is formed so that the thickness dimension et1 at the crucible body portion 7 is, for example, 15.0 mm or more and 17.0 mm or less. This is because if the thickness is more than 17.0 mm, the crystallized layer is too thick and it is difficult to obtain adhesion to the carbon crucible, and if it is less than 15.0 mm, it is difficult to obtain the contribution of improving durability. The thickness et2 of the first outer layer 2A constituting the outer layer 2 is thinner than the thickness et3 of the second outer layer 2B, and the ratio of the thickness et2 to the thickness et3 of the second outer layer 2B is, for example, 4:6.

[0023] Furthermore, the thickness dimension ct1 of the outer layer 2 at the crucible bottom corner 8, which is formed continuously from the outer layer 2 at the body portion 7, is formed to be 6 mm or more, and the thickness dimension bt1 of the outer layer 2 at the crucible bottom 9 is formed to be 6 mm or more. This is because if the thickness dimension ct1 of the outer layer 5 at the crucible bottom corner 8 and the thickness dimension bt1 of the outer layer 5 at the crucible bottom 9 are smaller than 6 mm, it is difficult to obtain sufficient durability. In the crucible bottom corners 8 and the crucible bottom 9, the ratio of the thicknesses ct2, bt2 of the first outer layer 2A to the thicknesses ct3, bt3 of the second outer layer 2B in the outer layer 2 is also set to 4:6 to 5:5.

[0024] The transparent inner layer 4 is a transparent layer that is substantially bubble-free and is formed by melting synthetic raw quartz glass (or natural raw quartz glass) that contains no more than 1 ppm of metal impurities, Na, K, and Al. In the transparent inner layer 4, the thickness dimension it1 at the crucible body portion 7, the thickness dimension it2 at the crucible bottom corners 8, and the thickness dimension it3 at the crucible bottom 9 are all formed to be 3 mm or more. This is because if the thickness of the transparent inner layer 4 is less than 3 mm, it is difficult to make the crystallization accelerator concentration on the inner surface of the transparent inner layer 4 in contact with the silicon melt sufficiently low, for example, to 1 ppm or less.

[0025] According to the quartz glass crucible 1 having such a structure, in the initial stage of the start of pulling the silicon single crystal, the outer layer 2 at the crucible bottom corner 8 and the crucible bottom 9 softens and adheres to the carbon susceptor supporting the crucible 1. In addition, since the second outer layer 2B having a low bulk density (having large-diameter bubbles) is formed thicker than the first outer layer 2A having a higher bulk density (having small-diameter bubbles) throughout the entire crucible, bubble expansion is promoted in the outer layer 2 when heated to a high temperature, the wall thickness expansion rate is improved, and adhesion to the carbon susceptor is improved, and collapse is suppressed. In addition, since the viscosity of the first outer layer 2A is increased, the occurrence of outward sinking deformation is suppressed even if the second outer layer 2B expands to a thick wall. Thereafter, from the start to the completion of pulling, the crystallization (cristobalite formation) of the outer layer 2 progresses due to high-temperature heating.

[0026] Next, a method for manufacturing the quartz glass crucible 1 having the above structure will be described. A silica glass crucible 1 is manufactured using a silica glass crucible manufacturing apparatus 10 as shown in Fig. 3. The crucible molding die of the silica glass crucible manufacturing apparatus 10 is composed of an inner member 12 made of a gas permeable material such as a metal mold having a plurality of through holes or a highly purified porous carbon mold, and a holder 14 that holds the inner member 12 and has a ventilation part 13 on its outer periphery.

[0027] A rotating shaft 15 connected to a rotating means (not shown) is fixed to the lower part of the holder 14, and rotatably supports the crucible forming mold 11. The ventilation section 13 is connected to an exhaust passage 17 provided in the center of the rotating shaft 15 through an opening 16 provided in the lower part of the holder 14, and this exhaust passage 17 is connected to a pressure reducing mechanism 18. An arc electrode 19 for arc discharge, a natural silica powder supply nozzle 22, and a high-purity synthetic silica powder supply nozzle 23 are provided at the upper portion facing the inner member 12.

[0028] When manufacturing a quartz glass crucible 1 using the quartz glass crucible manufacturing apparatus 10 configured in this manner, a rotary drive source (not shown) is operated to rotate the rotating shaft 18 in the direction of the arrow, thereby rotating the crucible forming mold 11 at high speed. Next, natural silica powder is supplied into the crucible forming mold 11 from the natural silica powder supply nozzle 22. The supplied natural silica powder is pressed against the inner surface of the inner member 12 by centrifugal force and formed into a green body for the outer layer 2 (step S1 in FIG. 4).

[0029] Next, high-purity synthetic quartz powder having metal impurity contents of Na, K, and Al of 1 ppm or less each is supplied from high-purity synthetic quartz powder supply nozzle 23 so that a transparent layer having a thickness of 3 mm or more is formed on the inner surface side of outer layer 2 (inner surface side of second outer layer 2B). The supplied high purity synthetic silica powder is pressed against the inner surfaces of the opaque intermediate layer 3 and the opaque outer layer 5 by centrifugal force, and is molded into a green body for the transparent inner layer 4 (Step S2 in FIG. 4).

[0030] In this manner, a crucible body having an outer layer 2 and a transparent inner layer 4 is obtained. Furthermore, the pressure inside the inner member (mold) 12 is reduced by operating the pressure reducing mechanism 18, and electricity is passed through the arc electrode 19 to heat the crucible body from inside, melting the transparent inner layer 4 and outer layer 2 of the crucible body in that order. Here, the pressure reduction output of the pressure reduction mechanism 18 is adjusted to adjust (change) the pressure within the inner member 12 during melting. Specifically, when the transparent inner layer 4 is melted, the pressure inside the inner member 12 is set to, for example, 2.0 to 8.0 kPa, and the transparent inner layer 4 is heated and melted (step S3 in FIG. 4).

[0031] In the subsequent melting of the outer layer 2, the second outer layer 2B is melted and formed first. When melting the second outer layer 2B, the pressure inside the inner member 12 is set to, for example, 98 kPa (close to atmospheric pressure) (step S4 in FIG. 4). In this state, the second outer layer 2B is melted until the thickness becomes, for example, 7.8 to 8.4 mm so that the thickness becomes thicker than the first outer layer 2A to be formed later (step S5 in FIG. 4). This increases the diameter of the bubbles present inside, and the second outer layer 2B is formed with low bulk density and low viscosity. With the second outer layer 2B having such characteristics, the bubble expansion at high temperatures increases the wall thickness expansion rate, improving adhesion to the carbon susceptor and making it difficult for the layer to collapse inward.

[0032] Subsequently, when the second outer layer 2B of the desired thickness is formed, the pressure in the inner member 12 is switched to a lower value, for example, 85 kPa, and the first outer layer 2A of, for example, 1 mm in thickness is melted (step S6 in FIG. 4). This reduces the diameter of the bubbles present inside, and the first outer layer 2A is formed with high bulk density and high viscosity. The first outer layer 2A with such characteristics has high viscosity at high temperatures, and is less likely to sink to the outside of the crucible.

[0033] In this manner, a quartz glass crucible 1 is manufactured in which the diameter of the bubbles present in the first outer layer 2A, which is the outermost layer 2, is smaller than the diameter of the bubbles present in the second outer layer 2B, which is the innermost layer, and the bulk density of the first outer layer 2A is smaller than the bulk density of the second outer layer 2B.

[0034] As described above, according to this embodiment, the first outer layer 2A, which is the outermost layer in the outer layer 2, has a smaller bubble diameter, and the second outer layer 2B, which is the innermost layer, has a larger bubble diameter. In addition, the first outer layer 2A is formed to have a smaller bulk density than the second outer layer 2B. As a result, in the second outer layer 2B, the wall thickness expansion rate increases due to bubble expansion at high temperatures, improving adhesion to the carbon susceptor, making it difficult for the crucible 1 to collapse inward. Also, in the first outer layer 2A, the viscosity increases at high temperatures, so that outward sinking deformation can be prevented even if the second outer layer 2B expands in the thickness direction. According to this embodiment, in forming the outer layer 2, a molded body is formed using quartz powder of the same particle size, and the mold pressure is changed when melting the molded body to form the first outer layer 2A and the second outer layer 2B having different bubble diameters. Therefore, the bubble diameter can be easily controlled, and the problem that the same quality cannot be maintained depending on the crucible can be solved.

[0035] In the above embodiment, a crucible having a three-layer structure in the body portion has been described as an example, but the present invention is not limited to this, and it is sufficient that the outer layer 2 has a structure having at least two layers. EXAMPLES

[0036] Next, the quartz glass crucible according to the present invention will be further described based on examples. In this example, a quartz glass crucible having the configuration shown in the above embodiment was manufactured and subjected to a heat treatment to verify its effect.

[0037] (Experiment 1) In Example 1, a quartz glass crucible having the layered structure shown in Fig. 1 was manufactured using the quartz glass crucible manufacturing apparatus shown in Fig. 3. At this time, the pressure in the inner member (mold) when melting the outer layer molded body was set to two stages to control the bubble size and bulk density. The pressure in the mold when melting the molded body for the outer layer was set to 98 kPa when forming the inner second outer layer constituting the outer layers, and 85 kPa when forming the outermost first outer layer. The duration of these set pressures was set to the same time when forming the first outer layer and when forming the second outer layer, so that they were formed to approximately the same thickness. In the manufactured quartz glass crucible, the bubble diameter and bulk density in the first outer layer and the second outer layer constituting the outer layer are as shown in Table 1. That is, in the first outer layer, the bubble diameter is 16 to 56 μm and the bulk density is 2.03 g / cm 3 In the second outer layer, the bubble diameter was 21 to 100 μm and the bulk density was 1.81 g / cm 3 It was.

[0038] [Table 1]

[0039] Next, this quartz glass crucible was used to heat the crucible to high temperatures in a furnace and pull up a silicon single crystal. As a result, no deformation such as collapse or sinking of the crucible was observed. Table 2 shows the number of bubbles, average bubble diameter, maximum bubble diameter, minimum bubble diameter, and bulk density in the outer layer of the quartz glass crucible after high-temperature heating.

[0040] [Table 2]

[0041] It is believed that the diameter of the bubbles in the second outer layer, which is thicker than the first outer layer, is large even after high-temperature heating as shown in Table 2, and therefore the thickness expansion rate is improved, and the adhesion to the carbon susceptor is improved, preventing collapse. In addition, the bulk density of the first outer layer is higher than that of the second outer layer even after high-temperature heat treatment, i.e., the viscosity is higher, so that even if the second outer layer expands to a thicker thickness, the first outer layer prevents sinking deformation.

[0042] Comparative Example 1 As Comparative Example 1, a quartz glass crucible was manufactured by consistently setting the pressure of the die when melting the molded body for the outer layer at 98 kPa. The other conditions were the same as those in Example 1. Next, the quartz glass crucible was heated to high temperatures in a furnace and a silicon single crystal was pulled up. As a result, the crucible did not collapse inward, but did sink outward.

[0043] Comparative Example 2 As Comparative Example 2, a silica glass crucible was manufactured by consistently setting the pressure of the die when melting the molded body of the outer layer at 85 kPa. The other conditions were the same as those of Example 1. Next, the quartz glass crucible was heated to a high temperature in a furnace to pull a silicon single crystal, which resulted in the crucible tipping over inward.

[0044] As a result of the above examples, it was confirmed that the quartz glass crucible of the present invention can effectively prevent deformation such as collapse or sinking of the crucible when heated at high temperatures. [Explanation of symbols]

[0045] 1. Quartz glass crucible 2 Outer layer 2A First outer layer 2B Second outer layer 4 Transparent inner layer 7 Straight body part 8 Bottom Corner 9 Bottom 10. Quartz glass crucible manufacturing equipment

Claims

1. In a quartz glass crucible for pulling a single crystal by the Czochralski method, a transparent inner layer; and an outer layer disposed outside the transparent inner layer and formed to be opaque by containing air bubbles; The outer layer includes a first outer layer and a second outer layer disposed on an inner side of the first outer layer, an average diameter of air bubbles present in the first outer layer is smaller than a diameter of air bubbles present in the second outer layer; The quartz glass crucible is further characterized in that the bulk density of the first outer layer is greater than the bulk density of the second outer layer.

2. The quartz glass crucible according to claim 1, characterized in that, in the outer layer, the thickness of the second outer layer is the same as or greater than the thickness of the first outer layer.

3. A quartz glass crucible as described in claim 1 or claim 2, characterized in that, in the outer layer, the average diameter of the bubbles present in the first outer layer is 16 to 56 μm, and the average diameter of the bubbles present in the second outer layer is 21 to 100 μm.

4. In the outer layer, the bulk density of the first outer layer is 1.96 g / cm 3 2.08g / cm or more 3 and the bulk density of the second outer layer is 1.74 g / cm 3 1.88g / cm or more 3 4. The quartz glass crucible according to claim 1, wherein:

5. A method for producing a quartz glass crucible according to any one of claims 1 to 4, rotating an inner member of the crucible mold around an axis and supplying a glass raw material powder to the inside of the inner member to form an outer layer; supplying a glass raw material powder inside the outer layer to form an inner layer to form a crucible molding; and heating and melting the crucible molded body from the inside to form a quartz glass crucible. A method for manufacturing a quartz glass crucible, characterized in that when the outer layer is heated and melted, the pressure inside the inner member is changed in two stages, the first stage being a weak reduced pressure condition and the second stage being a strong reduced pressure condition, thereby forming a first outer layer and a second outer layer having different average diameters of the bubbles contained therein.

Citation Information

Patent Citations

  • Quartz glass crucible and method of manufacturing the same

    JP2015127287A